Phonetics at Al-Kindi in his two treatises (The Lisp) and (blind extraction) (Journal of the College of Basic Education, 2022)
It is no secret to any of the scholars that they deny what the Muslim philosophers presented in terms of enriching thought. scientific study among the Arabs, and sound research was one of the sciences in which they cared a lot.The philosopher (*) was concerned with the phonetic aspect, especially in his treatises (Al-Lughtah) and (Extraction of the Blind) - which are The topic of research - through which he was able to present a valuable audio study that approximates recent results.His dissertation (Al-Lagha) was not limited to the study of defective speech (Lighta) alone, but the study had many aspects.